No Amplifications of Hypoxia-Inducible Factor-1α Gene in Invasive Breast Cancer: A Tissue Microarray Study - Marije M. Vleugel; Reinhard Bos; Horst Buerger; Petra van der Groep; Outi R. Saramäki; Tapio Visakorpi; Elsken van der Wall; Paul J. van Diest (Cellular Oncology)
Objective: Hypoxia Inducible Factor‐1 (HIF‐1) is an important transcription factor that stimulates tumour growth and metastases via several pathways, including angiogenesis and altered metabolism. Activation of HIF‐1 depends on the levels of its α‐subunit, which increase during hypoxia. Recent studies showed that the HIF‐1α gene was amplified in prostate cancer, leading to overexpression of HIF‐1α at normoxia. The aim of this study was to evaluate the presence of HIF‐1α gene amplifications in invasive breast cancer as an explanation for HIF‐1α protein overexpression. Methods: Protein and gene expression of HIF‐1α were analyzed on a tissue microarray of 94 breast cancers by immunohistochemistry and fluorescent in situ hybridization (FISH), respectively. Results: Overexpression of HIF‐1α protein was found in 58/94 (62%) of patients. No amplifications of the HIF‐1α gene were detected. Conclusion: Increased protein levels of HIF‐1α are not associated with amplification of the HIF‐1α gene in human breast cancer. Therefore, other mechanisms than gene amplification must be responsible for HIF‐α overexpression at normoxia.